Introductory note to the special issue on the social and solidarity economy - Afouxenidis, Alex; Petrou, Michael; Kavoulakos, Karolos Iosif (The Greek Review of Social Research, 2020)
This special issue is dedicated to the social and solidarity economy (SSE). The basic idea for this issue came out of a conference that was organized on this topic in Athens, on the 13th & 14th of March 2019. The organizer was the National Centre of Social Research (EKKE) in collaboration with the Department of Political Sciences from the Aristotle University of Thessaloniki. The term “SSE” is fundamentally descriptive and it helps us to analyze and perhaps better understand the multiple shapes and forms that associations, non-profits and co-operatives take, in an ever changing social and political environment.